The handicap principle : a missing piece of Darwin's puzzle - Zehavi, Amots (Oxford University Press, 1999)
Ever since Darwin, animal behavior has intrigued and perplexed human observers. The elaborate mating rituals, lavish decorative displays, complex songs, calls, dances and many other forms of animal signaling raise fascinating questions. To what degree can animals communicate within their own species and even between species? What evolutionary purpose do such communications serve? Perhaps most importantly, what can animal signaling tell us about our own non-verbal forms of communication? In The Handicap Principle, Amotz and Ashivag Zahavi offer a unifying theory that brilliantly explains many p.